Enhancing Oral Proficiency and Medical Communication in Medical English for Non-Native Speakers through Collaborative Strategies: A Case Study at Grigol Robakidze University - Lamara Kadagidze (European Scientific Journal, ESJ, 2025)
The research presented herein explores the effectiveness of a collaborative teaching approach in enhancing oral proficiency and medical communication in Medical English for non-native speaker students. A case study was conducted at Grigol Robakidze University (GRUNI) with first-year Medical Program (MP) students enrolled in a Medical English course, delivered through a partnership between a non-native speaker instructor and a native English language expert. Unlike a completely new initiative, this course was designed as a continuation of Medical English I, addressing the specific challenges identified during the previous semester. Students had already received prior instruction in Medical English, and their needs were carefully analyzed before implementing the revised course. The research employed a mixed-methods approach, utilizing surveys and interviews to evaluate students' progress, satisfaction, and perceptions of the course. Quantitative data focused on students’ self-assessed proficiency levels and confidence, while qualitative feedback provided deeper insights into their learning experiences. Results indicated significant improvements in students’ confidence and proficiency, with 60% reporting high confidence in presenting medical topics in English after the course. The collaborative teaching model, combining native and non-native instructors, was highly regarded by students (80% considered it very effective). Additionally, students identified reading academic texts and improving oral presentation skills as the most beneficial aspects of the course. The study highlights the value of integrating diverse teaching methodologies to enhance both linguistic skills and communication strategies in medical contexts. Based on student feedback, recommendations include increasing interactive learning opportunities such as role-playing exercises and peer-led discussions to further engage students in real-world medical scenarios.